INTEGRATED MARKETING COMMUNICATION (IMC) PT. INDOMARCO PRISTAMA DALAM MEMPERTAHANKAN LOYALITAS KONSUMEN DI PEKANBARU - Fitra Perawati (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
In the current era of globalization of business conduct, particularly the field of marketing has increased from the previous time. Currently, many company the race the race trying to increase competition and mastered by utilizing and applying the right marketing strategy. It is inevitable market control is one way company to sustain life. This study aims to find out what forms of IMC were conducted by PT Indomarco Prismatama in maintaining consumer loyalty in Pekanbaru and for any megetahui PT Indomarco Prismatama limiting factor in doing IMC. The method used in this research is qualitative method with descriptive presentation presented in the form of language description, this is subject in research development division (Development Division Manager), Division of Marketing (Marketing Franchise), head shops, and consumers. While the object of this research is an integrated marketing communications (Integrated Marketing Communication) PT.Indomarco Prismatama in maintaining consumer loyalty in Pekanbaru. Data collection techniques used are documentation, interviews, observation and study of literature, The results showed that the strategy undertaken by PT.Indomarco Prismatama in maintaining customer loyalty and rewarding so far functioning properly. Form of Integrated Marketing Communication (IMC) conducted PT.Indomarco Prismatama is through ads (advertising), sales promotion (sales promotion), public relations (publicity), direct marketing. Barriers in Integrated Marketing Communication (IMC) PT.Indomarco Prismatama in Pekanbaru is the lack of human resources that store employees serve customers who are less good.Keyword : IMC, Minimarket, Customer Loyalty